Oxidative stress-mediated abnormal polarization of decidual macrophages promotes the occurrence of atonic postpartum hemorrhage - Jiangxue Qu; Hai Jiang; Boyang Zhang; Huifeng Shi; Shuai Zeng; Wei Wang; Lian Chen; Yangyu Zhao (Redox Biology)
Postpartum hemorrhage (PPH) is the leading cause of maternal mortality worldwide. However, the mechanism underlying atonic PPH remains partially elucidated. Multi-omics revealed that differentially expressed proteins and metabolites were enriched in the immune-inflammation pathway in the vaginal blood of patients with atonic PPH. There was a pro-inflammatory immune microenvironment primarily activated by M1 macrophages in the decidua of the patients with atonic PPH, which presented as increased tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-8 levels and affected the contraction of the uterine smooth muscle. Besides, the decidual macrophage of the atonic PPH group exhibited increased oxidative stress. The PPH decidual cell culture medium induced the polarization of peripheral blood monocytes towards M1 macrophages while markedly increasing the levels of reactive oxygen species and superoxide anion radical. Using hydrogen peroxide (H2O2) to stimulate decidual macrophages induced a similar polarization state to that in atonic PPH samples, and the secretion of pro-inflammatory cytokines, such as TNF-α and IL-8, was significantly upregulated, which markedly impacted the expression of contraction-associated proteins (CAPs) in the uterine smooth muscle cells (uSMCs). The animal model suggested that H2O2 promoted the polarization of placental macrophages towards M1, affecting the levels of placental oxidative stress and inflammatory infiltration, and the contractility of uterine smooth muscle tissues. In summary, abnormal oxidative stress at the maternal-fetal interface induced the M1 polarization of decidual macrophages, causing the secretion of pro-inflammatory cytokines. TNF-α and IL-8 acted on uSMCs to inhibit CAP expression, inducing atonic PPH.